Synthesis and biological evaluation of benzenesulphonamide-bearing 1,4,5-trisubstituted-1,2,3-triazoles possessing human carbonic anhydrase I, II, IV, and IX inhibitory activity - Rajiv Kumar; Vikas Sharma; Silvia Bua; Claudiu T. Supuran; Pawan K. Sharma (Taylor & Francis Group, 2017)
A library of benzenesulphonamides incorporating 1,2,3-triazole rings functionalised with ester, carboxylic acid, carboxamide, carboxyhydrazide, and hydroxymethyl moieties were synthesised. The carbonic anhydrase (CAs, EC 4.2.1.1) inhibitory activity of the new compounds was assessed against four human (h) isoforms, hCA I, hCA II, hCA IV, and hCA IX. Among them, hCA II and IV are anti-glaucoma drug targets, being involved in aqueous humour secretion within the eye. hCA I was inhibited with Ki's ranging between 8.3 nM and 0.8737 µM. hCA II, the physiologically dominant cytosolic isoform, was excellently inhibited by these compounds, with Ki's in the range of 1.6-9.4 nM, whereas hCA IV was effectively inhibited by most of them, with Ki's in the range of 1.4-55.3 nM. Thirteen of the twenty sulphonamides were found to be excellent inhibitors of tumour associated hCA IX with Ki's ≤ 9.5 nM. Many of the new compounds reported here showed low nM inhibitory action against hCA II, IV, and IX, isoforms involved in glaucoma and some tumours, making them interesting candidates for further medicinal chemistry/pharmacologic studies.